The Reasons of Death among Children and Adolescents in Lorestan Province, West of Iran, from 2007 to 2014 - Astaraki, P; Mahmoudi, Gh; Ahadi, M; Almasi, Vahid (International Journal of Medical Toxicology and Forensic Medicine, 2016)
Background: The UNESCO, in the case of children's rights, has stressed that a child has a right to live in the best possible condition of health and hygiene as well as a safe and un-risky environment. Evaluation of the reasons for the death and mortality of children and adolescents can prevent similar deaths. The aim of this study was to evaluate the reasons of mortality among children and adolescents in Lorestan province. Methods: This cross-sectional study was conducted on children and adolescents (younger than 18 years old) in Lorestan province, west of Iran, in the period of 2007-2014 in Lorestan Legal Medicine Research Center. The demographic data of dead individuals, including age, sex and cause of death, were studied. The main reasons of death were classified in four main groups of trauma, asphyxia, poisoning, and miscellaneous causes (including physiological disease, infant insufficiency, cancer, and unknown cause). The data was analysed by the SPSS software (version 17). P value <0.05 was considered statistically significant. Results: In the period of 2007 to 2014, 1115 children died in Lorestan province, consisting of 634 (56.8%) boys and 481 (44.2%) girls. The highest mortality rate was observed in 15 to 18 year age group (n= 395, 35.4%). The most prevalent reasons of death were different types of trauma (65.3%), asphyxia (18%), miscellaneous causes (10.8%) and poisoning (5.8%). Conclusion: The outbreak of death and mortality in children and adolescents following trauma and accidents in our country seems significant in relation to the developing countries and few of the neighbouring countries. Considering the ability to carry out the preventative measures in this field, instantaneous policy making is needed in order to eliminate the present defects in the security provision to this group of society.